2000
DOI: 10.1258/0022215001906642
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for juvenile angiofibroma

Abstract: Juvenile angio broma presents characteristic imaging signs, many of which allow diagnosis and accurate estimation of extent without recourse to the dangers of biopsy. The diagnosis by computed tomography (CT) is based upon the site of origin of the lesion in the pterygopalatine fossa. There are two constant features: (1) a mass in the posterior nasal cavity and pterygopalatine fossa; (2) erosion of bone behind the sphenopalatine foramen with extension to the upper medial pterygoid plate. Good bone imaging on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 5 publications
2
62
0
10
Order By: Relevance
“…A convoluted cerebriform pattern is a reliable MR imaging feature of sinonasal inverted papillomas, but it is lacking in many cases (such an imaging feature was seen in 2 of the 7 present cases). 17 Signal-intensity voids are characteristic MR imaging features of angiofibromas with high vascularity, 18 but they also may be absent (seen in 2 of the 3 present cases). Finally, in the present study, there were no significant differences in overall ADCs or ADC mapping between inverted papillomas, angiofibromas, and hemangiomas (On-line Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 58%
“…A convoluted cerebriform pattern is a reliable MR imaging feature of sinonasal inverted papillomas, but it is lacking in many cases (such an imaging feature was seen in 2 of the 7 present cases). 17 Signal-intensity voids are characteristic MR imaging features of angiofibromas with high vascularity, 18 but they also may be absent (seen in 2 of the 3 present cases). Finally, in the present study, there were no significant differences in overall ADCs or ADC mapping between inverted papillomas, angiofibromas, and hemangiomas (On-line Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 58%
“…Involvement of various areas as seen on preoperative imaging forms the basis for all the staging systems for JNA Diagnosis of Juvenile nasopharyngeal angiofibroma is based on history, clinical examination and imaging studies. Nasopharyngeal angiofibroma presents with typical radiological signs that aids in preoperative diagnosis without subjecting the patients to the perils of a biopsy [6]. Lloyd et al [6] reported two characteristic features suggesting a diagnosis of JNA, a soft tissue mass in the posterior nasal cavity and pterygopalatine fossa with erosion of posterior osseous margin of the sphenopalatine foramen extending to the base of the medial pterygoid plate.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal angiofibroma presents with typical radiological signs that aids in preoperative diagnosis without subjecting the patients to the perils of a biopsy [6]. Lloyd et al [6] reported two characteristic features suggesting a diagnosis of JNA, a soft tissue mass in the posterior nasal cavity and pterygopalatine fossa with erosion of posterior osseous margin of the sphenopalatine foramen extending to the base of the medial pterygoid plate. The finding of the anterior bowing of the posterior wall of the maxillary sinus on plain X-ray, was described by Holman and Miller as 'antral sign'(Holman Miller sign).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative investigations include imaging and endoscopy [5]. Computerized tomography, MRI and arteriography are valuable diagnostic procedures in the evaluation of angiofibromas [10]. Arteriography clearly demonstrates vascular pattern and blood flow dynamics and allows preoperative selective embolization to reduce intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%